Exploring the Importance of Halal Tourism: Cultural Influences on Travel Accommodation Choices Among Middle-Class “Santri” in West Java - Amin, Ali; Semmawi, Ramli; Dewi , Subkhani Kusuma (International Journal of Islamic Business and Economics (IJIBEC), 2024)
This article aims to investigate the limited development of Syariah-certified hotels in Indonesia despite the country’s substantial potential in the global halal tourism market. Indonesia has actively promoted halal certification in the accommodation and hospitality industries, supported by central and regional governments. These initiatives align with Islamic hospitality principles, including halal-certified food, the prohibition of alcohol, modest dress codes for employees, and gender-segregated facilities. However, despite the rising discourse on halal tourism, the number of Syariah-certified hotels remains disproportionately low. This study seeks to understand why this gap exists and how the Muslim community perceives Syariah-compliant accommodations. Observations and interviews with 38 middle-class santri groups in West Java, particularly in the Jabodetabek area, reveal that their choice of accommodation is influenced more by cultural factors than religious ideology. Despite being religiously literate, many santri do not prioritize Syariah hotels when traveling. These findings highlight a disconnect between the supply of and demand for Syariah hotels, providing insights into the cultural and practical challenges facing halal tourism development in Indonesia.